Efeito do tratamento da aloe vera no diabetes: estudo por análise proteômica da expressão de proteínas no rim - Santos, Lilian dos [UNIFESP] (2016)
Diabetes mellitus (DM) is a metabolic syndrome characterized by chronic hyperglycemia, with diabetic nephropathy (ND) as its complication. Several studies have demonstrated that Aloe vera (A. vera) has beneficial effects on DM and its consequences. Proteomic analysis is a tool that systematically studies the set of proteins expressed in a given situation. Therefore, the aim of this study was to evaluate the effect of DM1 on the kidney through proteomic analysis, comparing with animals without DM, besides evaluating the effect of insulin treatment and the buthanolic fraction of A. vera (FB) in order to elucidate the protective mechanism of this plant in renal injury induced by this pathology. The streptozotocin-induced diabetic model was used in male Wistar rats. We observed a hypoglycemic effect of FB, which was able to reduce glycemia lasting up to 6 hours after treatment. There was a statistically significant increase in serum creatinine in the untreated (D) and insulin treated (INS) groups compared to the control group (C). On the other hand, there was no difference in relation to urinary creatinine and creatinine clearance. All groups presented increased 24h proteinuria in relation to the C group. The D group presented some alterations in the histological analysis, with dilated tubules and hyperfiltrant glomeruli. The diabetic group treated with FB presented a discrete but not significant improvement. Proteomic analysis identified 93 proteins with statistical differences between the C and D groups, being 36 proteins related to diabetes, and were grouped into: proteins related to mitochondrial dysfunction, arginine metabolic process, eicosanoic acid eicosatrienoic acid, lactate production, glycolysis/pentoses pathway, lipid metabolism, stress, inflammation, calcium influx, transport and others. In addition, 5 exclusive proteins of group D were found, being 2 proteins related to this syndrome. FB treatment was shown to have a beneficial effect, altering the expression of 11 of these proteins, besides presenting two exclusive proteins. Thus, A. vera may be a promising ally in the treatment of diabetes and kidney damage prevention.